PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn DENGAN METODE PROBLEM SOLVING - Fadillah, Fadillah; Reinita, Reinita; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research is aimed to describe the improvement of the students’ learning outcomes in learning the Civics Subject by Using the Problem Solving Method at 4th grade of SDN 02 Kubang. The classroom-action research is conducted in the research by using both qualitative and quantitative approaches. The subjects of the research were the teacher and 18 students of the school. The results of the research shows that there are an improvement on the plan,act,and students’ learning outcome. Thus,the use of Problem Solving Method has improved the students’ learning outcome in learning the Civics Subject. Keyword: Learning outcome, Problem Solving Method